Coordination of stomata and vein patterns with leaf width underpins water‐use efficiency in a C4 crop. (28th November 2021) - Pan, Ling; George‐Jaeggli, Barbara; Borrell, Andrew; Jordan, David; Koller, Fiona; Al‐Salman, Yazen; Ghannoum, Oula; Cano, Francisco J.
Abstract: Despite its importance for crop water use and productivity, especially in drought‐affected environments, the underlying mechanisms of variation in intrinsic water‐use efficiency ( iWUE  = net photosynthesis/stomatal conductance for water vapour, g sw ) are not well understood, especially in C4 plants. Recently, we discovered that leaf width ( LW ) correlated negatively with iWUE and positively with g sw across several C4 grasses. Here, we confirmed these relationships within 48 field‐grown genotypes differing in LW in Sorghum bicolor, a C4 crop adapted to dry and hot conditions. We measured leaf gas exchange and modelled leaf energy balance three times a day, alongside anatomical traits as potential predictors of iWUE . LW correlated negatively with iWUE and stomatal density, but positively with g sw, interveinal distance of longitudinal veins, and the percentage of stomatal aperture relative to maximum. Energy balance modelling showed that wider leaves needed to open their stomata more to generate a more negative leaf‐to‐air temperature difference, especially at midday when air temperatures exceeded 40°C. These results highlight the important role that LW plays in shaping iWUE through coordination of vein and stomatal traits and by affecting stomatal aperture. Therefore, LW could be used as a predictor of higher iWUE among sorghum genotypes. Summary statement: Leaf width ( LW ) plays an important role in shaping intrinsic water‐use efficiency ( iWUE ) across Sorghum bicolor genotypes through coordination of vein and stomatal traits and by regulating stomatal aperture. Wider leaves had higher g sw likely to prevent a detrimental rise in leaf temperature. Therefore, LW could be used as a predictor for higher iWUE among sorghum genotypes